The endangered species Brycon orbignyanus: genetic analysis and definition of priority areas for conservation - Ashikaga, Fernando Yuldi [UNESP]; Orsi, Mario Luis; Oliveira, Claudio [UNESP]; Senhorini, Jose Augusto; Foresti, Fausto [UNESP] (Springer, 2015)
Currently, biodiversity is threatened by several factors often associated with human population growth and the extension of areas occupied by human activity. In particular, freshwater fish fauna is affected by overfishing, deforestation, water pollution, introduction of exotic species and habitat fragmentation promoted by hydroelectric dams, among other environmental impact factors. Several action plans to preserve ichthyofauna biodiversity have been adopted; however, these plans frequently cover only a small number of species, and decisions are often made without strong scientific support. This study aimed to evaluate the genetic aspects of wild groups of Brycon orbignyanus, an endangered fish species, using microsatellites and D-loop regions to identify the genetic structure of the samples and to establish priority areas for conservation based on the genetic patterns of this species. The results indicated that the samples showed levels of genetic variability compatible with others studies with Neotropical fishes. However, the results obtained in the analysis of molecular variance (AMOVA) for microsatellites (F (ST) = 0.258) and D-loop (F (ST) = 0.234) and the interpopulation fixation index revealed that B. orbignyanus was structured in different subpopulations in the La Plata River basin; the areas with better environmental conditions also showed subgroups with higher rates of genetic variability. Future conservation actions addressing these sites should consider two different management units: the complex formed by the Ivinhema River, Upper Parana, Camargo Port and Ilha Grande groups; and the complex formed by the Verde River and Sucuriu River groups.
Keywords: Genetic conservation; Genetic structure; Genetic variability; Freshwater fish; Migratory species; Environmental management